2019
DOI: 10.1158/1055-9965.epi-18-1095
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Infection is a Prognostic Biomarker for Better Survival in Operable Esophageal Cancer: Analysis of 2,004 Patients from an Endemic Area in China

Abstract: Background: Hepatitis B Virus (HBV) infection has been proven to be associated with the survival of many cancers. However, the prevalence and prognostic value of HBV infection in esophageal cancer has not been investigated yet. Methods: A total of 2,004 consecutive esophageal cancer patients who underwent esophagectomy between 2000 and 2008 were recruited in our study. ELISA was used to test serum HBV markers. Patients were divided into HBsAg-positive group (HBV infection) and HBsAg-negative group. The impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…It is noteworthy that in our study, HBsAg did not increase the rate of liver metastases for very young patients with breast cancer. This results are comparable to those reported in previous studies for esophageal cancer and colorectal cancer (20,31), which suggested that HBV infection is associated with decreased risk of liver metastasis in these malignancies. Our study shows that HBsAg-positive status is associated with inferior DFS and OS in young patients with curatively resected breast cancer, decreasing the 10-year DFS and OS by 6.7 and 12.6%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is noteworthy that in our study, HBsAg did not increase the rate of liver metastases for very young patients with breast cancer. This results are comparable to those reported in previous studies for esophageal cancer and colorectal cancer (20,31), which suggested that HBV infection is associated with decreased risk of liver metastasis in these malignancies. Our study shows that HBsAg-positive status is associated with inferior DFS and OS in young patients with curatively resected breast cancer, decreasing the 10-year DFS and OS by 6.7 and 12.6%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that in our study, HBsAg did not increase the rate of liver metastases for very young patients with breast cancer. This results are comparable to those reported in previous studies for esophageal cancer and colorectal cancer ( 20 , 31 ), which suggested that HBV infection is associated with decreased risk of liver metastasis in these malignancies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We identified consecutive patients with esophageal cancer who underwent radical surgery for esophageal carcinoma at Sun Yat-sen University Cancer Center between December 2000 and December 2008 [15]. Patients who had received neoadjuvant or adjuvant therapy, had a history of other cancer, lacked weight loss date were excluded.…”
Section: Patientsmentioning
confidence: 99%